REFLECTIONS ABOUT THE ECHO OF THE EMPLOYEES IN THE ECONOMIC ENTITY’S SOUND - Dana-Florina PERȚE; Luminița RUS; Dana Simona GHERAI; Mărioara BELENEȘI (Oradea Journal of Business and Economics, 2025)
The importance of the employee’s contribution to the development of the business of an economic entity starts from the quality of the work performed and the quantity of the object of activity achieved, culminating in the efficiency of the work performed. This research aims to present the information contained in various reports regarding employees and the activities they carry out in the company. The analyzed reports concern the echo of the financial indicators felt by employees (salary, rewards, loyalty, etc.), as well as by the company (labor productivity, turnover, etc.). Information on the professional training of current and future employees is tracked and collected from non-financial reporting. Information on achieving the Sustainable Development Goals is analyzed from sustainability reporting. The analysis of the annual reports is carried out by companies in the energy sector and concerns only the 2023 annual reporting. The conclusions drawn refer to the way in which companies choose to disclose the role of employees in the company, the importance of the activity carried out by them, but also the actions they take to motivate and retain employees.